ANALYSIS OF TECHNICAL AND FINANCIAL FEASIBILITY STUDY OF PROJECT DEVELOPMENT RENOVATION OF KAPUAS INDAH MARKET PROJECT AND PUBLIC SERVICE MALL - Saffanah, Sasqia Nur; Lusiana, Lusiana; Syahrudin, Syahrudin (Fakultas Teknik Universitas Tanjungpura, 2023)
Each district or city is required to establish a Public Service Mall for services to the community, therefore the Government wants to make the Kapuas Indah Market building multifunctional which has been neglected for a long time by having a Public Service Mall on the 3rd floor of the Kapuas Indah Market with a total building area of ± 7,380m2. The construction of this renovation will certainly have various impacts so it is necessary to carry out a feasibility study in terms of technical and financial aspects.Analysis of the technical aspects carried out is based on the Basic Building Coefficient (KDB) of 78.79%, Building Floor Coefficient (KLB) of 2.36, Green Area Coefficient (KDH) of 21.20%, Parking Space Requirement of 581SRP, and Accessibility The locations reviewed are in accordance with applicable regulations and guidelines that the technical aspects of the renovation of the construction of the Kapuas Indah Market and Public Service Mall can be said to be feasible or have met the requirements in the construction of a project. While the results of the financial feasibility analysis show that the renovation project for the construction of the Kapuas Indah market and the Public Service Mall is feasible (profitable) because the results obtained using the Net Present Value (NPV) obtained a value of Rp. 10,223,725,624 1, the value of the Benefit Cost Ratio (BCR) of 1.1409 ³ 1 , the Internal Rate Of Return (IRR) is 7.78% MARR, and the Payback Period (PP) value is 22 years 11 months 14 days the investment plan age is 30 years. The sensitivity results show that the feasibility assessment of financial parameters is very sensitive to the IRR parameters for increasing expenses and decreasing revenue costs.